Rock mechanics in underground construction : ISRM International Symposium 2006 : 4th Asian Rock Mechanics Symposium, 8-10 November 2006, Singapore - Leung, C. F.; Zhou, Yingxin (World Scientific Pub. Co., 2006)
This proceedings volume contains over 300 papers on rock mechanics and engineering with contributors from all over Asia and many other parts of the world. Seven keynote papers summarize the state-of-the-art in rock engineering including topics such as underground rock caverns. The technical papers cover a wide range of rock mechanics and engineering topics such as: rock tunnels, caverns, mining, rock slopes and dams, rock blasting, rock burst and failure, rock properties, rock mass, rock joints, and block theory. Numerous valuable rock engineering case studies are also reported. This volume should serve as a useful reference for the engineers and researchers in rock mechanics and rock engineering.